Traditional Healing Practices Among First Nations Students - Wyrostok, Nina C.; Paulson, Barbara L. (Canadian Journal of Counselling and Psychotherapy, 2007)
Traditional Native healing practices are an important aspect of the First Nations peoples' conception of health and well-being. The purpose of this study was to assess post-secondary First Nations students' attitudes toward traditional Native healing practices. First Nations adult volunteers were surveyed in several adult educational settings to appraise their attitudes towards traditional healing practices in terms of their interest, valuing, and participation. The majority of subjects reported having participated in a diversity of Native healing practices. Implications of the prevalence of these beliefs and practices are discussed and recommendations for counsellors are offered.